The School Principal's Strategy In Improving School Branding - Umi Iriani; Muhammad Syaifuddin; Mudasir Mudasir (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study is motivated by the growing importance of school branding as a strategic approach to strengthening public trust amid increasing competition among educational institutions. Nevertheless, many public schools in semi-rural areas continue to struggle to develop a strong institutional image because branding is often perceived as seasonal promotional activities rather than a long-term strategic process. This study aims to analyze the principal's strategies for strengthening school branding at UPT SMP Negeri 3 Kampar, identify supporting and inhibiting factors, and formulate an appropriate branding model for public schools in semi-rural contexts. A qualitative case study approach was employed. Data were collected through in-depth interviews, participant observation, and document analysis involving the principal, vice principals, teachers, public relations personnel, and parents. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, including data reduction, data display, and conclusion drawing, supported by triangulation and member checking to ensure credibility. The findings reveal that school branding is strengthened through teacher professionalism, religious and character-based school culture, optimization of visual identity, intensive use of digital media, and the principal's relational engagement with the local community. These integrated strategies successfully enhanced public trust, reflected in the significant increase in student enrollment during the 2025/2026 academic year. The novelty of this study lies in proposing a hybrid school branding model that integrates local social capital, adaptive leadership, school culture, and digital communication to improve the competitiveness of public schools in semi-rural areas through a sustainable and community-oriented approach.